Comparative Transcriptome Sequencing Analysis of Hirudo nipponia in Different Growth Periods - Ma, Xiaocong; Yan, Xiuying; Ke, Ren; Shan, Huiquan; Rehman, Saif ur; Feng, Tong; Zheng, Yalin; Chuang, Chen; Zhou, Weiguan; Liu, Qingyou; Zheng, Jinghui (Frontiers in Physiology, 2022)
Hirudo nipponia is the only blood-sucking leech included in Chinese Pharmacopoeia having distinct features of anticoagulation, exorcizing blood stasis, and promoting menstruation. Despite such significant characteristics, very little is known about its molecular genetics and related physiological mechanisms. In this study, the transcriptomes of Hirudo nipponia at three developmental stages (larvae, young, and adults), revealed a total of 1348 differentially expressed genes (DEGs), 223 differentially expressed lncRNAs, and 88 novel mRNAs. A significant diverse gene expression patterns were observed at different developmental stages which were analyzed by differential gene expression trends, and the overall gene expression trends consist of three overall down-regulated trends, and two overall up-regulated trends. Furthermore, the GO and KEGG enrichment functional annotation analysis revealed that these DEGs were mainly associated with protein hydrolysis, signal transduction, energy metabolism, and lipid metabolism while. growth, development, metabolism, and reproduction-related DEGs were also found. Additionally, real-time quantitative PCR results confirmed deep sequencing results based on the relative expression levels of nine randomly selected genes. This is the first transcriptome-based comprehensive study of Hirudo nipponia at different developmental stages which provided considerable deep understanding related to gene expression patterns and their relevant developmental pathways, neurodevelopmental and reproductive characteristics of the leech.